SISTEM PENDUKUNG KEPUTUSAN DALAM PEMBERIAN BONUS BERDASARKAN PENILAIAN KINERJA KARYAWAN PADA CV. ABC DENGAN MENGGUNAKAN METODE ANALITYCAL HIERARCHY PROCESS (AHP) - Baringin Beri Sianipar; Dedi Candro Parulian Sinaga (Journal of Information System, Informatics and Computing, 2020)
In each company, agency, organization or business entity will provide a salary as compensation for the work of an employee, in addition to providing basic salary to employees, each agency often provides a bonus in addition to the basic salary to boost the performance and work productivity of its employees. The method for giving bonuses is by evaluating employees who meet the criteria by the leadership, bonuses will be given after an annual evaluation of the employee's assessment. The criteria that will be used to determine which employees have priority in order to get bonuses include attendance, appearance, discipline, communication, cooperation. In addition to still using conventional systems, the closeness of leaders and employees often results in decisions that are different from what they should be. This causes the results of their decisions to be incorrect. The problem in this research is how to build a decision support system using the Analytical Hierarchy Process (AHP) method. This method was chosen to help company leaders determine which employees are entitled to receive an annual bonus based on predetermined criteria.